Role of β‐lactamase residues in a common interface for binding the structurally unrelated inhibitory proteins BLIP and BLIP‐II. (1st July 2014) - Fryszczyn, Bartlomiej G.; Adamski, Carolyn J.; Brown, Nicholas G.; Rice, Kacie; Huang, Wanzhi; Palzkill, Timothy
Abstract The β‐lactamase inhibitory proteins (BLIPs) are a model system for examining molecular recognition in protein‐protein interactions. BLIP and BLIP‐II are structurally unrelated proteins that bind and inhibit TEM‐1 β‐lactamase. Both BLIPs share a common binding interface on TEM‐1 and make contacts with many of the same TEM‐1 surface residues. BLIP‐II, however, binds TEM‐1 over 150‐fold tighter than BLIP despite the fact that it has fewer contact residues and a smaller binding interface. The role of eleven TEM‐1 amino acid residues that contact both BLIP and BLIP‐II was examined by alanine mutagenesis and determination of the association (kon) and dissociation (koff) rate constants for binding each partner. The substitutions had little impact on association rates and resulted in a wide range of dissociation rates as previously observed for substitutions on the BLIP side of the interface. The substitutions also had less effect on binding affinity for BLIP than BLIP‐II. This is consistent with the high affinity and small binding interface of the TEM‐1‐BLIP‐II complex, which predicts per residue contributions should be higher for TEM‐1 binding to BLIP‐II versus BLIP. Two TEM‐1 residues (E104 and M129) were found to be hotspots for binding BLIP while five (L102, Y105, P107, K111, and M129) are hotspots for binding BLIP‐II with only M129 as a common hotspot for both. Thus, although the same TEM‐1 surface binds to both BLIP and BLIP‐II, the distribution of binding energy on the surface is different for the two target proteins, that is, different binding strategies are employed.